If f(x)=−x2−8x+7 and g(x)=x−1, what does (g−f)(x) equal? A)(g−f)(x)=−x2−9x+8 B)(g−f)(x)=−x2−7x+6 C)(g−f)(x)=−8x+8 D)

Question

If f(x)=−x2−8x+7 and g(x)=x−1, what does (g−f)(x) equal?
A)(g−f)(x)=−x2−9x+8
B)(g−f)(x)=−x2−7x+6
C)(g−f)(x)=−8x+8
D)(g−f)(x)=x2+9x−8

in progress 0
Nho 7 months 2021-07-17T15:31:13+00:00 1 Answers 4 views 0

Answers ( )

    0
    2021-07-17T15:32:21+00:00

    Answer is D we just have to subtract f(x) from g(x)

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )